PERHITUNGAN SIFAT FISIKA TANAH PADA DAS KURANJI BAGIAN HULU DAN TENGAH DI KOTA PADANG - Teguh Haria Aditia Putra, S.Pd M.P (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
Research calculations physical properties of soil in the watershed Kuranji upper and middle parts of Padang was held in October 2016 to November, 2016. This study aimed to calculate the physical properties of the soil (Heavy volume, total pore space, permeability, infiltration, Texture, soil structure) on each unit of land. This study used survey method and sampling using purposive random sampling. Research results vary greatly on each unit of land. On forest land units obtained a low volume weight ie (0.948 and 1.138 g / cm3) and the highest in paddy land units with a value of 1.311 g / cm3. Total Pore Space lowest for the wetland units (51.19%) and the highest in forest land units with a value between (59.27 to 69.95%). Soil permeability was lowest for the units of residential land values (1.88 and 1.92 cm / hour) and the highest in the forest land units (3.84 to 7.80 cm / hour). Infiltration smallest land units pemukimandan contained in a rice field with value (0.1 cm / hour), while the largest value found on forest land units with a value (4.1 to 12.4 cm / h). The dominant clay soil texture except at forest land with no samples 11 and 12. The structure in each unit of land that is glob angle. Keywords: Heavy volume, total pore space, permeability, infiltration, Texture, soil structure